“TEACHING VISUAL LITERACY AND ARTISTIC PERCEPTION IN FINE ARTS LESSONS: PEDAGOGICAL APPROACHES” - Qudratova Gulizuhro Otabek qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article examines pedagogical approaches to teaching visual literacy and artistic perception in fine arts lessons. Visual literacy enables students to interpret, analyze, and create visual content effectively, while artistic perception develops their ability to appreciate and respond to aesthetic elements. The study explores strategies for integrating theoretical knowledge, practical exercises, and interactive technologies to enhance students’ analytical, creative, and perceptual skills.